Networks in Aviation Strategies and Structures - Goedeking, Philipp. (Springer Berlin Heidelberg : Imprint: Springer, 2010)
Aviation networks play a critical role in the success of todays airlines and airports. This book provides insight on all aspects of modern network strategies and structures, ranging from market research to hub design, operations, organization, alliances, benchmarking, and antitrust issues. Considering both the airline and the airport perspectives, the book explains the economics of connectivity or productivity-driven hub structures through basic mathematics, which helps the reader to comprehend the structural strengths and weaknesses of aviation networks. More than 100 charts help clarify the topics at hand.